Constraints on spin-dependent short-range interaction between nucleons - Tullney, Kathlynne; Allmendinger, Fabian; Burghoff, M.; Heil, W.; Karpuk, S.; Kilian, W.; Knappe-Grüneberg, S.; Müller, W.; Schmidt, Ulrich; Schnabel, A.; Seifert, F.; Sobolev, Yu.; et al. (Physical review letters, 2013)
We search for a spin-dependent P- and T-violating nucleon-nucleon interaction mediated by light pseudoscalar bosons such as axions or axionlike particles. We employ an ultrasensitive low-field magnetometer based on the detection of free precession of colocated 3He and 129Xe nuclear spins using SQUIDs as low-noise magnetic flux detectors. The precession frequency shift in the presence of an unpolarized mass was measured to determine the coupling of pseudoscalar particles to the spin of the bound neutron. For boson masses between 2 and 500 μeV (force ranges between 3×10−4 m and 10−1 m) we improved the laboratory upper bounds by up to 4 orders of magnitude.
Gesehen am 14.02.2022